Recovery of cephalosporin C from aqueous solution using polymeric adsorbent - Mishra P.; Srivastava P.; Kundua S. (My University, 2025)
Commercially available neutral polymeric sorbents are used for recovery of beta lactam antibiotic cephalosporin C (CPC), from aqueous solution. The objective of this work is to evaluate the separation of CPC from fermentation broth during purification process. The neutral forms of CPC are preferentially adsorbed onto the neutral sorbents. Adsorption of CPC was higher onto the aromatic (XAD 4) as compared to aliphatic ester sorbent (XAD 8). The kinetics of CPC adsorption on aromatic polymeric adsorbent has been investigated. Isopropyl alcohol solution was used to desorb CPC.